Added value of rapid respiratory syndromic testing at point of care versus central laboratory testing: a controlled clinical trial. (23rd September 2021) - Bouzid, Donia; Casalino, Enrique; Mullaert, Jimmy; Laurent, Odile; Duval, Xavier; Lescure, François Xavier; Peiffer Smadja, Nathan; Tubiana, Sarah; Armand Lefèvre, Laurence; Descamps, Diane; Fidouh, Nadhira; Choquet, Christophe; et al.
Abstract: Background: Virus-associated respiratory infections are in the spotlight with the emergence of SARS-CoV-2 and the expanding use of multiplex PCR (mPCR). The impact of molecular testing as a point-of-care test (POCT) in the emergency department (ED) is still unclear. Objectives: To compare the impact of a syndromic test performed in the ED as a POCT and in the central laboratory on length of stay (LOS), antibiotic use and single-room assignment. Methods: From 19 November 2019 to 9 March 2020, adults with acute respiratory illness seeking care in the ED of a large hospital were enrolled, with mPCR performed with a weekly alternation in the ED as a POCT (week A) or in the central laboratory (week B). Results: 474 patients were analysed: 275 during A weeks and 199 during B weeks. Patient characteristics were similar. The hospital LOS (median 7 days during week A versus 7 days during week B, P =  0.29), the proportion of patients with ED-LOS <1 day (63% versus 60%, P =  0.57) and ED antibiotic prescription (59% versus 58%, P =  0.92) were not significantly different. Patients in the POCT arm were more frequently assigned a single room when having a positive PCR for influenza, respiratory syncytial virus and metapneumovirus [52/70 (74%) versus 19/38 (50%) in the central testing arm, P =  0.012]. Conclusions: Syndromic testing performed in the ED compared with the central laboratory failed to reduce the LOS or antibiotic consumption in patients with acute respiratory illness, but was associated with an increased single-room assignment among patients in whom a significant respiratory pathogen was detected.